Facilities management in sport training centre / Norliana Ghani - Ghani, Norliana (2008)
Talking about Facility Management, people might get confused in what is that thing refer to. Facility Management is an influential facility information management system. It provides the capability to manage the whole facility. It is all about the way on how to manage and admin the functional of such building includes its services and operational. Services are being categorized into two types; hard services and soft services.